Pengelolaan Kualitas Layanan Di Palms Restaurant Holiday Inn Resort Baruna Bali - I Made Bayu Wisnawa; Arief Nugraha Utomo; Ni Nyoman Rusmiati (Universitas Triatma Mulya, 2025)
The hospitality industry in Bali continues to experience rapid growth, increasing competition among hotels and restaurants to provide high-quality services that satisfy customers. This study focuses on Palms Restaurant at Holiday Inn Resort Baruna Bali, aiming to identify the challenges faced by management in enhancing waiter service quality and to analyze the strategies implemented to overcome these challenges. Using a descriptive qualitative approach, data were collected through direct observation, interviews with management and staff, and documentation during the period from January to May 2025. The research revealed that management struggles with uneven waiter skill levels, ineffective internal communication, and operational pressures during peak times. To address these issues, a holistic management approach was adopted, emphasizing cleanliness, consistent service delivery, responsiveness to customer complaints, and personalized, empathetic interaction. Regular training, briefings, and evaluations were pivotal in maintaining service reliability and customer trust. The study contributes to the body of knowledge by providing empirical evidence on effective management practices in the hospitality sector that improve service quality and customer satisfaction. Practically, it offers actionable insights for hotel restaurants aiming to enhance waiter performance and operational efficiency. Future research is recommended to explore deeper psychological and motivational factors affecting waiter performance and to investigate the impact of digital communication and ordering systems on operational efficiency and service excellence.